Removal of chrome dye from aqueous solutions by mixed adsorbents: Fly ash and coal - Gupta G.S.; Prasad G.; Singh V.N. (My University, 2025)
The removal of Omega Chrome Red ME (a popular chrome dye) from its aqueous solutions by adsorption on a homogeneous mixture of fly ash and coal in different proportions has been carried out. It has been noted that low adsorbate concentration, small particle size of adsorbent, low temperature and acidic medium favour the removal of the dye. A 100% removal of the said dye was achieved at 10 mg1-1, 30°C, 2.0 pH and 53 μm particle size, using a 1:1 ratio of fly ash and coal. The kinetics and mass transfer studies were made using the models suggested by Lagergren and McKay et al. respectively. The equilibrium data fit well in the Langmuir model of adsorption, showing the formation of monolayer coverage of dye molecules at the outer surface of the adsorbent. Effect of temperature was explained on the basis of solubility and chemical potential of the adsorbate. An attempt has been made to explain the results thus obtained on the basis of various physiochemical properties of the solid-solution interface involved in the process of removal. © 1990.